2021
DOI: 10.1080/00202967.2021.1956813
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the electroforming process: significance and challenges

Abstract: Electrochemical forming (or electroforming), is gaining recognition as an additive and sustainable manufacturing process. Electroforming could shape part of the fourth industrial revolution through thoughtful and systematic modelling. For this to be useful, efficient simulation of the electroforming process in 4.0 era should be used as a tool to design, test and propose optimised processes. Emphasis should be put on building models that provide new information about the electrochemical systems under investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Moving forward, Figure 4 presents the deposit thickness profiles (reflecting the current distribution) predicted for the two different reactors. In general, the current is predicted to be higher at the edges than at the centre of the disk as would be expected (Andreou and Roy, 2021). Consequently, increase in thickness profiles was predicted at the edges.…”
Section: Control Simulationsmentioning
confidence: 49%
See 2 more Smart Citations
“…Moving forward, Figure 4 presents the deposit thickness profiles (reflecting the current distribution) predicted for the two different reactors. In general, the current is predicted to be higher at the edges than at the centre of the disk as would be expected (Andreou and Roy, 2021). Consequently, increase in thickness profiles was predicted at the edges.…”
Section: Control Simulationsmentioning
confidence: 49%
“…Based on such information, certifiable models and new methodologies for controlling the thickness of an electroform, its uniformity and shape evolution could be developed. The authors have already discussed the state-of-the-art studies of modelling the electroforming process in a previous review paper (Andreou and Roy, 2021). However, it is important to briefly present here some of the most influential works-to the authors' opinion-on modelling other metal electrodeposition processes, which have reported findings that are proven to be a potent starting point for the studies focusing on modelling the electroforming process itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It will lead in less process waste, decreased inventory demand, potential compliance with environmental requirements, and supply chain optimization. 118 The most competitive industrial manufacturers have been working to make industrial manufacturing large volume, low cost, while maintaining high quality, and sustainable. Being an additive manufacturing process electroforming generates a limited amount of waste during manufacturing, aligning with sustainability goals by minimizing resource consumption and environmental effect.…”
Section: Significance and Challenges Of Electroforming Modellingmentioning
confidence: 99%